Activation of renal epithelial Na+ channels (ENaC) in infants with congenital heart disease - Ortmann, Laura A.; Nandi, Shyam; Li, Yu-long; Zheng, Hong; Patel, Kaushik P. (Frontiers in Pediatrics, 2024)
Introduction This study was designed to measure the concentration and activity of urinary proteases that activate renal epithelial sodium channel (ENaC) mediated Na+ transport in infants with congenital heart disease, a potential mechanism for fluid retention. Methods Urine samples from infants undergoing cardiac surgery were collected at three time points: T1) pre-operatively, T2) 6–8 h after surgery, and T3) 24 h after diuretics. Urine was collected from five heathy infant controls. The urine was tested for four proteases and whole-cell patch-clamp testing was conducted in renal collecting duct M-1 cells to test whether patient urine increased Na+ currents consistent with ENaC activation. Results Heavy chain of plasminogen, furin, and prostasin were significantly higher in cardiac patients prior to surgery compared to controls. There was no difference in most proteases before and after surgery. Urine from cardiac patients produced a significantly greater increase in Na+ inward currents compared to healthy controls. Conclusion Urine from infants with congenital heart disease is richer in proteases and has the potential to increase activation of ENaC in the nephron to enhance Na+ reabsorption, which may lead to fluid retention in this population.